Răspunderea șefului de stat: concept și forme - Tataru, Gheorghi (SUPREMANCE OF LAW, 2016)
Article includes some reflections on the institution Head of State liability being elucidatedforms and the grounds on which may occur. The author draws attention to the forms of liability Moldovan President governed by the law in force, and on the facts for which they can intervene. Consequently concludes about the forms of legal liability which is liable Moldovan President: criminal liability constitutional liability, contravention liability and civil liability.